2015
DOI: 10.1097/dad.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Granular Cell Tumor of the Arm

Abstract: Congenital granular cell tumors are uncommon benign tumors of newborns that mainly affect oral mucosa, especially the maxillary alveolar ridge. They are predominantly seen in female newborns, and cutaneous involvement is extremely rare. In this report, we present a case of congenital granular cell tumor on the arm of one of the male monozygotic twins and discuss the differential diagnosis of granular cell phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In 285 reported cases, CGCT being a benign tumour associated with the jaw was reported along with a 10% occurrence of intraosseous cases of arm[ 4 5 ] and other extra-alveolar sites. Aetiology being unknown like in our case, the hypothesis correlating with hormonal imbalance was correlated by injecting oestrogen in the uterine cervix of newborn mice.…”
Section: Discussionmentioning
confidence: 99%
“…In 285 reported cases, CGCT being a benign tumour associated with the jaw was reported along with a 10% occurrence of intraosseous cases of arm[ 4 5 ] and other extra-alveolar sites. Aetiology being unknown like in our case, the hypothesis correlating with hormonal imbalance was correlated by injecting oestrogen in the uterine cervix of newborn mice.…”
Section: Discussionmentioning
confidence: 99%
“…Only congenital GCT, "congenital epulis," that affects the oral mucosa differs pathologically from acquired cases of GCT and stains negatively for S100 indicating their nonneural origin. 17,66 Apart from suspected malignant lesions, surgical excision is the preferred treatment strategy for GCTs. 12 Careful assessment of the tumor margins during surgery is essential to avoid recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Only congenital GCT, “congenital epulis,” that affects the oral mucosa differs pathologically from acquired cases of GCT and stains negatively for S100 indicating their nonneural origin. 17,66…”
Section: Discussionmentioning
confidence: 99%
“…The predilection site is the alveolar ridge, on which the maxilla occurs more frequently than the mandible at a ratio of 3:1 (5). However, Çerman et al recently reported a rare case in the arm (6). The size ranges from several millimeters to a few centimeters (5).…”
Section: Clinical and Pathological Characters Of Cgctmentioning
confidence: 99%